A measurement of the configuration of a building enterprise management structure / Statybos įmonės valdymo struktūros konfigūracijos matavimas - Ginevičius, Romualdas (Journal of Civil Engineering and Management, 1996)
The configuration of a building enterprise management structure represents the outer form of a management system and is determined by two main principles of organizational formation, namely by specialization and coordination. The configuration may be measured by an organigram of an enterprise, i.e. by a graphical figure of a management system. A management system can be quantitatively characterized by 2 values: an average number of hierarchical management level and an average number of institutions at one hierarchical level. A generalized index of a building enterprise management structure configuration may be expressed by the product or ratio of the above-mentioned values. Which of them reflects better the real situation? Only an empirical investigation can reveal it. Article in Lithuanian. First Published Online: 26 Jul 2012